2019
DOI: 10.22266/ijies2019.1031.11
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Near Duplicate Image Retrieval Using SURF and CNN Features

Abstract: In this paper, we present an adaptive approach in order to match and retrieve near duplicate images at different scales. Matching only local Features does not necessarily identify visually similar images. Global features are fast at matching but less accurate. Many existing methods either use local features or CNN features for image or video retrieval task. In this paper, we combined the use of SURF local points and CNN features extracted around SURF points in order to match near duplicate image pairs. Image p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Smaller the block size, higher the number of CNN features and vice versa. However, in this experiment we followed the same block size mentioned in [9]. Performance improvement is found due to obtaining CNN for all selected local blocks as well as global (entire image).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Smaller the block size, higher the number of CNN features and vice versa. However, in this experiment we followed the same block size mentioned in [9]. Performance improvement is found due to obtaining CNN for all selected local blocks as well as global (entire image).…”
Section: Resultsmentioning
confidence: 99%
“…2) Improvement in our previous approach [9]: We found that retrieving images based on considering only local image regions may not always give correct results. The proposed technique extracts local CNN features as well as global CNN features from images.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For Human Object Identification for Human-Robot Interaction, Fast R-CNN is used in [13], and hybrid Fuzzy-CNN in [14]. Besides, the implementation of CNN has been used for many applications, such as for matching near duplicate image [15], for situation prediction and sentiment analysis [16,17], for handwritten recognition [18], and for human brain segmentation in medical [19].…”
Section: Introductionmentioning
confidence: 99%